Rapid climatic events and long term cultural change: the case of the Portuguese Upper Paleolithic - Bicho, Nuno Gonçalo Viana Pereira Ferreira (2019)
In Western Europe, the Upper Paleolithic is marked by clear regional and diachronic technological differences. Some of these are most likely related with human adaptations to the Late Pleistocene environmental shifts. In this paper we focus on the rapid climatic change events and their influence on the Iberian regional ecology and vegetation cover. Based on those changes and their impact on the main Upper Paleolithic cultural phases in central and southern Portugal, we propose an explanatory model, to be tested in the future, where rapid climatic events, such as the D-O and Heinrich Events, have direct impact on the ecology and vegetation cover and this, in turn, cause changes in human adaptations in terms of mobility, settlement patterns, land use and technology. (C) 2015 Elsevier Ltd and INQUA. All rights reserved.